2019
DOI: 10.12765/cpos-2019-02
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Intentions across Immigrant Generations in Sweden. Do Patterns of Adaptation Differ by Gender and Origin?

Abstract: In being representative of individuals’ demographic value orientations, fertility preferences provide information about immigrants’ adaptation to family formation patterns in the destination country at a deeper, ideational level than actual fertility does. Using data from Wave 1 of the Swedish GGS from 2012/2013 (n=3,932), this study compares the first, 1.5, and second generations with either one or two foreign-born parent(s) to Swedes without an immigrant background by gender and across origins. Binary logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 59 publications
(135 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, our results suggest that the neighbourhood composition's association with fertility adaptation persists among child migrants, and possibly among the second generation. This finding resonates with studies which have provided evidence that among immigrants from high-fertility settings, the convergence of fertility behaviour can take at least two generations (Milewski 2010;Scott and Stanfors 2011;Kulu et al 2017;Pailhé 2017;Carlsson 2019). Finally, these implications also seem to be associated with the contexts in which the proportion of co-ethnic immigrants is relatively moderate, at least when considered at the country level.…”
Section: Summary and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, our results suggest that the neighbourhood composition's association with fertility adaptation persists among child migrants, and possibly among the second generation. This finding resonates with studies which have provided evidence that among immigrants from high-fertility settings, the convergence of fertility behaviour can take at least two generations (Milewski 2010;Scott and Stanfors 2011;Kulu et al 2017;Pailhé 2017;Carlsson 2019). Finally, these implications also seem to be associated with the contexts in which the proportion of co-ethnic immigrants is relatively moderate, at least when considered at the country level.…”
Section: Summary and Discussionsupporting
confidence: 83%
“…Recent studies that explore the adaptation perspective have involved the 1.5 generation, i.e. individuals who migrated as children (Bleakley and Chin 2010;Adserà et al 2012), and second-generation immigrants (Parrado and Morgan 2008;Kulu and Hannemann 2016;Kulu et al 2017;Pailhé 2017;Guarin Rojas et al 2018;Carlsson 2019).…”
Section: Theoretical Perspectives and Previous Findingsmentioning
confidence: 99%
“…In the European context, evidence from Sweden shows convergence to destination country short-term intention patterns, with the second generation being similar to non-migrants. The first generation instead shows more positive short-term fertility intentions compared to natives, while the 1.5 generation occupies an intermediate position (Carlsson 2018). Puur et al (2018) recently studied the fertility intentions of Russian migrants and their descendants in Estonia, comparing non-migrants in Estonia and Russia.…”
Section: Fertility Intentions In the Short Termmentioning
confidence: 99%
“…Research has shown the persistence of patterns similar to those in the country of origin (i.e. non-migrant peers) among first-generation migrants, while demonstrating a gradual convergence towards patterns typical of natives among those in the 1.5 and second generations (Carlsson 2018;Puur et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research on migrants’ fertility intentions has only been addressed in a small number of studies (e.g. Carlsson, 2018; Mussino et al, 2021). Most of these studies address very specific cases (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%